(untitled) (Ornitología Colombiana, 2021)
Henicorhina negreti is reported from the Department of Antioquia in the Western Andes of Colombia, 350 km north of the type-locality. This finding implies that the species is much more widespread than previously thought and calls for a reexamination of its conservation status.